(3GdehGAeI Hjf ecGaBJ CYVGA gjFI GdJOQjS h QSGdI GdeDSSIs (3GdHjGfGJ, h GdSjGSGJ, h GdEQTGOGJs - (3OGjGehfO, QhHQJ Ees; (3GdedGM, YeQhs; (3LGHQ, YHO GdeWdH jhSas ((3GdQjGVs (3ecJHI GdYHjcGfs, 2006)
(3jhaQ gPG GdcJGH EQTGOGJ dJWhjQ fXGe eJeGSc decGaBJ CYVGA gjFI GdJOQjS, jHOC HJhVjM ChdhjGJ GdeDSSI h jJYbH GdYedjI YHQ JWhjQ EQTGOGJ GdbSes
(3GdeMJhjGJ (B: (3JWhjQ fXGe efGSH h aGYd decGaCI gjFI GdJOQjS(B: (3GdNUGFU h GdTQhW GdVQhQjI (B-- (3JdHjI GdMGLI Gdi EOQGL fXGe ecGaBJ dgjFI GdJOQjS (B-- (3JWhjQ HjGf QSGdI GdeDSSI (B-- (3JWhjQ EQTGOGJ GdeDSSI h GdcdjIs
1 9 12
Keywords: (3GdJYdje GdLGeYis; (3GdJYdje GdYGdis; (3GdLGeYGJ h GdcdjGJs -- (3JfXje h EOGQIs